Evolution of Project Management in the Digital Economy - Cabeças, António (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The great changes caused by the Fourth Industrial Revolution, also known as Digital Transformation, are happening very fast. We are living a new reality of Digital Economy, where technological innovation has a great impact on how projects are managed. This article has the objective to identify what Project Managers appropriate profile should be in order to face this new reality, taking advantage of using new digital technologies to increase the probability of projects' success and contribute with added value to the economy, the environment, and society. It is also presented the model proposed by Green Project Management, oriented to sustainability, and is also emphasized the importance of identifying the best approach to follow in the development of a new project in this Digital Economy era, knowing that besides the traditional predictive and agile approaches, there are rising new hybrid approaches, gathering the positive characteristics of the both of them.